18FDG PET/CT in Routine Surveillance of Asymptomatic Patients following Treatment of Sinonasal Neoplasms. (15th August 2017) - Workman, Alan D.; Glicksman, Jordan T.; Parasher, Arjun K.; Carey, Ryan M.; Brooks, Steven G.; Kennedy, David W.; Nabavizadeh, Seyed A.; Learned, Kim O.; Palmer, James N.; Adappa, Nithin D.
Abstract : Objective: Sinonasal neoplasms have a high rate of recurrence following treatment, and current guidelines support the use of a variety of surveillance techniques. Recent work demonstrates that performance parameters of surveillance modalities may differ with sinonasal tumors in particular when compared with head and neck tumors overall. This study aims to characterize the value of 18 fluorodeoxyglucose ( 18 FDG) positron emission tomography/computed tomography (PET/CT) as a screening tool in asymptomatic patients. Study Design: Retrospective cohort study. Setting: Hospital of the University of Pennsylvania and Pennsylvania hospital. Methods: Records of asymptomatic patients without suspicious endoscopy or suspicious imaging other than PET during the first 3 years following definitive treatment for sinonasal malignancy were screened and analyzed for inclusion in the cohort. Disease recurrence was determined by biopsy following suspicious PET evaluation. Results: PET/CT scans (n = 111) were performed for 45 disease‐free asymptomatic patients with no evidence of disease on endoscopy, and 6.3% were suspicious and prompted biopsy during this period, revealing 3 cases of disease recurrence. Overall specificity for PET/CT alone was 96.3% (95% CI, 90.7%‐99.0%), with a negative predictive value of 99% (95% CI, 94.8%‐100%). All recurrences were detected between 7 and 12 months, and all patients with true recurrence diagnosed by PET/CT had extrasinonasal involvement of tumor at the time of surgery. Conclusion: We examined performance parameters of 18 FDG PET/CT in asymptomatic patients with no evidence of disease on endoscopy during the posttreatment period for sinonasal malignancy. The ability of PET/CT to detect recurrences that may be missed by structural imaging or endoscopy makes it a valuable tool for clinicians.